Microgrid simulation and modeling for a utility in southern Negros Oriental, Philippines - Tuballa, Maria Lorena (2019)
An increasingly distributed energy future means localized generation at the distribution level. This means higher efficiency and helps decarbonize our energy system. The challenge for utilities is to adapt to emerging technologies and evolve but connecting renewable energy into existing systems is not without costs. With optimization tools like HOMER, the task of determining the most cost-effective system becomes simpler and faster. This paper aims to determine the optimal renewable energy source for a utility coverage area. Negros Oriental in the Philippines has abundant solar radiation most times of the year. Based on National Renewable Energy Laboratory data, it has considerable potential for wind energy. The area also has the potential for small hydro. The study obtains the costs and the possible configurations for the distribution system. It uses actual load profiles recorded by the utility. The study has also looked at publications that used HOMER as a tool, ascertaining its influence in the simulation of microgrids. The optimal system combination for the area is Grid and 40 Vestas 82 Wind Turbines. The effect of reduced wind speeds and a higher power price is noted. While many similar studies stop at obtaining the most cost-effective system, this paper has a section on post-HOMER discussion that inspects the implications of the results.